The 49th mystic - Dekker, Ted, 1962- (Dekker, Ted, 1962- Beyond the circle., 2018)
Some say the great mystery of how one can live in two worlds at once died with Thomas Hunter many years ago. Still others that the gateway to that greater reality was and is only the stuff of dreams. They are wrong. In the small town of Eden, Utah, a blind girl named Rachelle Matthews is about to find out just how wrong. When a procedure meant to restore Rachelle's sight goes awry, she begins to dream of another world so real that she wonders if Earth might only be a dream experienced when she falls asleep in that reality. Who is a simple blind girl to have such strange and fantastic dreams? She's the prophesied one who must find and recover five ancient seals--in both worlds--before powerful enemies destroy her. If Rachelle succeeds in her quest, peace will reign. If she fails, both worlds will forever be locked in darkness. So begins a two-volume saga of high stakes and a mind-bending quest to find an ancient path that will save humanity. The clock is ticking; the end rushes forward.